Design and synthesis of 2, 6-disubstituted-8-amino imidazo[1, 2a]pyridines, a promising privileged structure. Issue 12 (23rd July 2018) - Boulahjar, Rajaa; Rincon Arias, Angela; Bolteau, Raphaël; Renault, Nicolas; Coevoet, Mathilde; Barczyk, Amélie; Duroux, Romain; Yous, Saïd; Melnyk, Patricia; Agouridas, Laurence
Graphical abstract: Abstract: Imidazo[1, 2 a ]pyridines have gained much interest in the field of medicinal chemistry research. In the aim of accessing new privileged structure, we decided to design and synthesize 8-aminated-imidazo[1, 2 a ]pyridines substituted on positions 2 and 6. This scaffold, rarely found in the literature, was obtained via palladium-catalyzed coupling reactions (Suzuki reaction or N -hydroxysuccinimidyl activated ester method) and tested on adenosine receptor A2A . We demonstrated how incorporation of an exocyclic amine enhanced affinity towards this receptor while maintaining low cytotoxicity.